A diagnosis of agricultural health in Jamaica - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This document has the long-term objective in modernizing the agricultural health in Jamaica is: to provide the necessary agricultural health and food safety systems so that animal and plant products for export can meet the sanitary and phytosanitary requirements to compete successfully in international markets. To ensure that imported food is safe for consumers and free fromo pests and diseases that may threaten local agricultural production.